Biological activity of different forms of oxidized parathyroid hormone - Hasan, Ahmed A.; Hocher, Carl-Friedrich; Kleuser, Burkhard; Krämer, Bernhard; Hocher, Berthold (International journal of molecular sciences, 2022)
Preclinical studies have shown that parathyroid hormone (PTH) loses its biological effects through oxidation. PTH can be oxidized at methionines 8 and 18. Three possible variations of oxidized PTH (oxPTH) exist: Met8(ox)PTH, Met18(ox)PTH, and Met8, Met18(di-ox)PTH. A recent study showed that Met18(ox)PTH retained biological activity and was able to upregulate Fgf23 gene expression, whereas Met8(ox)PTH and Met8, Met18(di-ox)PTH showed less or no biological activity. An earlier study likewise showed that the oxidation of Met18 has minor effects on the secondary structure of PTH, whereas the oxidation of Met8 causes substantial structural changes, consistent with another study showing that oxidization just at Met8 blocks the generation of the second messenger cAMP, whereas the effect of the oxidation of Met18 is much less potent in inhibiting cAMP formation. A considerable percentage of circulating PTH in chronic kidney disease (CKD) patients is oxidized. However, we do not know the relative amounts of the different forms of oxPTH with agonistic, partial agonistic, or even antagonistic biological actions in different CKD populations. This might explain different clinical findings in the different CKD populations analyzed so far. The currently available method that was used in these clinical studies just distinguishes between oxPTH and noxPTH without being able to differentiate between different forms of oxPTH. Only methods of PTH measurement that are able to differentiate between PTH forms (noxPTH, Met8(ox)PTH, Met18(ox)PTH, and Met8, Met18(di-ox)PTH) have the potential to improve patient care, because only these methods will definitively separate bioactive from non-bioactive PTH forms. Such methods need to be developed, validated, and used in prospective randomized clinical trials to define the potential value of bioactive PTH forms as a predictor of cardiovascular events, mortality, and bone turnover.